Lexicon of medieval nordic law - Love, Jeffrey Scott (Open Book Publishers, 2020)
This volume is an indispensable resource for scholars and students of medieval Scandinavia. This polyglot dictionary draws on the vast and vibrant range of vernacular legal terminology found in medieval Scandinavian texts - terminology which yields valuable insights into the quotidian realities of crime and retribution; the processes, application and execution of laws; and the cultural and societal concerns underlying the development and promulgation of such laws.